Language Learning in the Time of COVID-19: ELT Students’ Narrated Experiences in Guided Reflective Journals - Wilson, Amanda; Lengeling, M. Martha (Íkala, Revista de Lenguaje y Cultura, 2021)
This article presents the results of a qualitative study of the lived experiences and emotional responses regarding language learning of 29 students in a bachelor’s degree in English language teaching (elt) offered at a public university in central Mexico. The study was grounded in sociocultural theory and was carried out at a time when the students’ classes changed overnight to online learning due to the worldwide covid-19 pandemic. In this program, students learn a foreign language within a theoretical framework of second language acquisition (sla) and document their language learning experience (lle) through reflective journals. One month into the new online modality, they were asked to write in their journals about a historical artifact that would represent their experience during the pandemic for a historian 100 years in the future. A constant comparative method of analysis of their narrated stories reveals the challenges faced and ensuing emotions: from overwhelming anxiety to youthful optimism. These results provide an appreciation of students’ complex emotions regarding their language learning process while in the midst of a worldwide pandemic and highlight the importance of creating activities that promote reflection.